Presence of SARS-CoV-2 RNA in human corneal tissues donated in Italy during the COVID-19 pandemic. Issue 1 (10th June 2022) - Ferrari, Stefano; Franco, Elena; Del Vecchio, Claudia; Zorzi, Ilaria; Fasolo, Elisa; Crisanti, Andrea; Ponzin, Diego
Abstract : Objective: To analyse corneal tissues from asymptomatic donors with a postmortem nasopharyngeal swab tested positive for the presence of SARS-CoV-2 RNA, and therefore, understand the role that corneal transplantation may have in viral transmission. Methods and analysis: Between March 2020 and October 2021, 101 corneas (out of 8154 collected in Italy) from 51 donors (out of a total of 4155 Italian donors) positive for SARS-CoV-2 after postmortem nasopharyngeal swab tests were analysed for the presence of SARS-CoV-2 RNA through real-time RT-PCR. When available, the corneal tissue storage media were also assessed. Corneas and/or storage media with confirmed presence of SARS-CoV-2 RNA were further investigated by isolating SARS-CoV-2 virions, which were used to infect VeroE6 target cells. Results: Only N=4 corneas and/or storage media out of 101 showed presence of SARS-CoV-2 RNA. No VeroE6 cell infection was detected with viral isolates, thus suggesting no presence of SARS-CoV-2 virions in corneal specimens and storage media. Conclusions: The presence of SARS-CoV-2 in cornea specimens would seem to be more likely due to prolonged detection of RNA rather than to active viral replication, with very low risk of infectivity and transmission through keratoplasty.